2008
DOI: 10.1007/s00425-008-0862-6
|View full text |Cite
|
Sign up to set email alerts
|

Galactose metabolism in cell walls of opening and senescing petunia petals

Abstract: Galactose was the major non-cellulosic neutral sugar present in the cell walls of 'Mitchell' petunia (Petunia axillaris x P. axillaris x P. hybrida) flower petals. Over the 24 h period associated with flower opening, there was a doubling of the galactose content of polymers strongly associated with cellulose and insoluble in strong alkali ('residual' fraction). By two days after flower opening, the galactose content of both the residual fraction and a Na(2)CO(3)-soluble pectin-rich cell wall fraction had sharp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…3; Supplementary Table S3). This fits well with the documented profound structural and morphological changes that occur in petal cell walls of flowers as they open and senesce (O’Donoghue et al , 2009; O’Donoghue and Sutherland, 2012). …”
Section: Resultssupporting
confidence: 88%
“…3; Supplementary Table S3). This fits well with the documented profound structural and morphological changes that occur in petal cell walls of flowers as they open and senesce (O’Donoghue et al , 2009; O’Donoghue and Sutherland, 2012). …”
Section: Resultssupporting
confidence: 88%
“…A similar case has been reported in strawberry fruit where Fabgal1 and Fabgal2 seem to be having longer sequences than Fabgal3 due to the presence of SUEL-type lectin domain at their C-termini (Trainotti et al 2001). The presence of lectin-like domain at the C-terminus has also been characterized in Cicer arietinum (Esteban et al 2005) and petunia petals (O'Donoghue et al 2009). The existence of this lectin-like domain in radish recombinant enzyme rRsBGAL1 seemed to have effects on its specific activity since it was ten times more than that of the native b-galactosidase, RsBGAL1, which lacked the domain (Kotake et al 2005).…”
Section: Discussionmentioning
confidence: 71%
“…It has been reported that galactose is an important component of the xyloglucans in the primary cell wall [62]. Nevertheless, free galactose has severe inhibitory effects on certain aspects of plant growth and development even at very low concentrations [21], [57], [63], and its inhibitory effect on auxin-induced growth could be explained by the inhibition of IAA transport [57].…”
Section: Discussionmentioning
confidence: 99%